Pengaruh Kompleksitas Operasi, Solvabilitas dan Profitabilitas Terhadap Audit Report Lag Pada Perusahaan Manufaktur Yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2020 - Jannah, Siti Raudhatul; Muhammad Ridha Habibi Z; Marwan Faiz Hilmi; Jeremia Pamurah Situmeang (Politeknik Ganesha Medan, 2024)
The problem in this research is the Audit Report Lag, namely the delay in submitting the company's financial statements on the IDX beyond the specified time limit , namely the end of the fourth month , will be subject to sanctions in the form of payment of fines . The purpose of this study was to determine and analyze the effect of operating complexity, solvency, and profitability on audit report lag in manufacturing companies listed on the Indonesia Stock Exchange in 2019-2020. The population in this study are all manufacturing companies on the IDX in 2019-2020. The data collection technique used is purposive sampling method, with a total sample of 49 companies. The period contained in this study is 2 years, namely 2019-2020 so that the research data becomes 98. The research data analysis method uses logistic regression analysis with SPSS test equipment. The results showed that operating complexity had no significant effect on Audit Report Lag, Solvency had no significant effect on Audit Report Lag. Meanwhile, Profitability had a significant effect on Audit Report Lag. Simultaneously Operational Complexity, Solvency, and Profitability have no effect on Audit Report Lag. These results indicate that there are still many variables outside the research variables that can explain Audit Report Lag. The conclusion of this study is that the complexity of operations and solvency do not affect the length of time span for submitting financial statements, but companies must pay attention to regulations regarding the deadline for publication of financial statements.